Симон Петлюра в памяти своих соратников в период межвоенной Волыни - Davydiuk, Ruslana (Pamięć i Sprawiedliwość, 2018)
The emergence of Ukrainian political emigration on the territory of the Second Polish Republic was due to the defeat of the Ukrainian revolution. The desire to settle on the territory of the Volyn Voivodship was motivated by the people’s eagerness to get into the Ukrainian-language, mostly Orthodox religious environment, which reduced the intensity of the psychological adaptation of the emigrants. The figure of Symon Petliura was controversially evaluated by various political environments, however, in the Volyn Voivodship, the chieftain’s companions treated him mainly respectfully. Starting from 1926, every year in May throughout all western Volyn mourning events took place in the form of memorial services, academies, presentations of abstracts. In the regional centers there were Ukrainian public committees to commemorate the memory of Petliura. The sympathizers of Symon Petliura offered the format of celebrations, their ideological content, celebrated the honor of the Chieftain by collecting funds for the assistance of the Symon Petliura Library in Paris and donations to the funds of the Museum of the Liberation Movement of Ukraine in Prague. Remembrance of the name of Symon Petliura played an important role in unifying emigration, the formation of historical memory. The beginning of the Second World War interrupted this tradition on the territory.